Collaborative quality improvement strategy in secondary prevention of cardiovascular disease in India: findings from a multi-stakeholder, qualitative study using Consolidated Framework for Implementation Research (CFIR) - Singh, Kavita; Huffman, Mark D.; Johnson, Leslie C. M.; Tandon, Nikhil; Prabhakaran, Dorairaj; Mendenhall, Emily (Global heart, 2022)
Cardiovascular disease (CVD) is highly prevalent in India, and little is known about the perception of patients and providers about a package of collaborative quality improvement (C-QIP) strategies consisting of provider-focused electronic health records-decision support system (EHR-DSS), non-physician health workers (NPHW), and patient-facing text messages to enhance the CVD care.